Patient’s Perceptions of Anti-Cancer Chemotherapy Side Effects and Adherence on Treatment at Mbarara Regional Referral Hospital - Okiria, Julius Okiror; Beinempaka, Florence (Student's Journal of Health Research Africa, 2023)
Background: Chemotherapy is one of the most common treatment modalities for cancer. However, despite the benefits of indicated chemotherapy, the side effects and toxicities of the treatment frequently affect the patient’s quality of life (QOL) and hence adherence to the treatment. The study aimed to examine the patient’s perception of the anti-cancer chemotherapy side effects and adherence to treatment at MRRH Methodology: The study utilized a descriptive qualitative design. It involved 40-60 minute in-depth interviews with 10 participants who had undergone chemotherapy treatment to understand their perceptions and their treatment adherence. Inductive thematic data analysis was used to generate themes and categories. Results: The following themes and categories emerged: Benefits [helpful, feeling good, believed getting better], and perceived severity [chemotherapy side effects, frustration, pain, and fear of death]. Conclusion: The perceived severity of the chemotherapy had a considerable impact on the patients’ quality of life. Despite these side effects experienced by most of the participants, the benefits of chemotherapy and considerable support from staff influenced the participants to adhere to treatment. Recommendations: There is a need for health workers to continue providing the necessary information about the disease, the drugs, the course of treatment, and the prognosis to improve patient acceptance of the chemotherapy
Keywords: Patient’s perceptions; Adherence; Anti-cancer chemotherapy